Biosensors in food safety and quality : fundamentals and applications - Mishra, Poonam; Pratim Sahu, Partha (Electronics engineer) (CRC Press, 2022)
"Biosensors in Food Safety and Quality: Fundamentals and Applications have become indispensable in today's world due to the requirement of food safety and security for human health and nutrition point of view. This book covers various types of sensors and biosensors that can be used for food safety and food quality monitoring but not limited to conventional sensors including temperature sensors, optical sensors, electrochemical sensors, calorimetric and pH sensors. It is framed in such a way where readers can experience the novel fabrication procedures of some advanced sensors including lab-on-a-chip biosensors, IOT based sensors, microcontroller-based sensors, and so on particularly for fruits and vegetables, fermented products, plantation products, dairy based product, heavy metal analysis in water, meat, fish etc. Its simplistic presentation and pedagogical writing style may provide the necessary thrust and adequate information to beginners, scientists, and researchers. The book offers comprehensive coverage of the most essential topics, including: fundamentals of biosensors, overview of food safety and quality analysis, major toxicants of food and water, and fabrication technique of biosensors applicable for different sections of food industries. This book serves as a reference book for scientific investigators, who works on assurance of food safety and security using biosensing principle, as well as researchers developing biosensors for food analysis. It may also be used as a textbook for a graduate level course in bioelectronics"- Resumé vydavatel
Keywords: biosenzory; bezpečnost potravin; analýza potravin; analytická chemie; biosensors; food safety; food analysis; analytical chemistry; elektronické knihy; kolektivní monografie; electronic books; collective monographs